(untitled) (Environment & Health, 2021)
Objective: We determined the possible effects of priority chemical environmental carcinogens on the incidence of hormone-dependent tumors and the mechanisms of their effect on the basis of the analysis of literature data and our own research. Results: The performed analysis demonstrates the scanity of the research devoted to the study of chemical carcinogens which are concerned only with the class of polycyclic aromatic hydrocarbons (PAH), benzo(a)pyrene (BP), atmospheric pollution, emissions from vehicles, the cadmium heavy metal and products of smoking containing these substances. The connection with PAH (BP) and the development of breast, ovarian cancer, cadmium with the development of breast, endometrial, ovarian cancer in women and prostate cancer in men was established. Epidemiological data, combined with experimental ones, suggest a possible contribution of carcinogens into the increase of the incidence of hormone-dependent tumors. At the same time, mechanisms of action of PAH and cadmium on the development of hormone-dependent tumors are unclear. The accumulated experimental and epidemiological data allow us to conclude that the oncological danger of these carcinogens lies in the combination of genotoxic and hormone-mimetic properties; the main mechanisms, involved in the realization of the effect of BP and cadmium, are associated with changes and disorders at different levels of the structural and functional organization of the organism, including the endocrine system, which can lead to the development of tumors. The urgency of the problem of the incidence of hormone-dependent tumors and the potential role of the studied chemical carcinogens as pollutants of the environment of human functions indicate the need to take these circumstances into account when developing and implementing preventive measures.